Cultural Management Case Study Puppet Show Luang Prabang City, Luang Prabang Province - HAEKHAM, Sonesay; KEOBOALAPHET , Soulideth; VONGCHUANGTHAM, Bountheing (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
This research paper aims to 1. Study the elements in the transmission of e-pok puppet theatre and 2. Analyze the reality of the persistence of e-pok puppet theatre in Luang Prabang province. The research method is to collect field data by interviewing. The sampling of this research was the village chief, five community members, ten respondents from the Luang Prabang province's department of information culture and tourism, the head of Phalak-Phalam Lao theatre, and two outside experts. Its elements in the e-pok puppet show with the relevant parties and analyzing the reality of the existence of the e-pok puppet show in Luang Prabang province. The results of the study found that the elements created in the production of puppet theatre include 2 elements, which are material elements related to performance or transmission. There are many in the community and local area, such as equipment for making E-pok puppets. And non-material elements related to performance and transmission There are many things involved, such as puppet shows, literature, rituals for taking out the puppets and putting them in the box before and after the performance, and the sound of the drums and cymbals. As for the results of the study, the reality of the survival of the puppet show in Luang Prabang Province includes the risk of continuity, the practice of the community, the risk of succession, the risk of sustainability in access to the use of material elements and related resources, the survival of cultural heritage and other morals that are related to the performance of the puppet show, and the protection or other measures against the risk and encouraging the practice in the future and succession. There are many in the community and local area, such as equipment for making E-pok puppets.